Outlet Ownership in Franchising Systems: An Agency Based Approach - SESHADRI, Sudhi (Institutional Knowledge at Singapore Management University, 2002)
Building on prior agency theoretic explanations of the franchisor-franchisee relationship, this paper introduces the franchise system manager in the traditional dyadic channel. This allows the franchisors internal agency problems of providing incentives to managers to be linked to their external agency problems of acquiring and extracting rents from franchisees. The paper finds preliminary empirical support for this approach in a structural equations model estimated on a franchise system data set. It then develops and analyzes an agency-theoretic model with agency tradeoffs. An explicit rationale for mixed ownership in franchising emerges from the model, where the share of company owned outlets is endogenously determined as the tradeoff between franchisee rents and managerial compensation.